Conditions for establishment of a key restotation species, Lupinus elegans Kunth, in a a Mexican temperate forest - Diaz Rodriguez, B.=700 1 Del Val, E.; Gomez Romero, M.; Gomez Ruiz, P.A.; Lindic Cisneros, R.
(Es, En)
Ilus., 53 ref.
Keywords: LUPINUS; FABACEAE; GERMINACION; VEGETACION; MEXICO; LUPINUS ELEGANS